Teacher preparation for local development project on students’ self-conduct - Autthapon Intasena; Apantee Poonputta (International Journal of Evaluation and Research in Education (IJERE), 2022)
The research aimed at studying the effects of the teacher preparation for local development project on students’ self-conduct. It was also comparing the conduct of students who studied in different years. The sample group of 189 was selected through multi-stage random sampling technique. The research instruments comprised the questionnaire and interview regarding the effects of joining the teacher preparation for local development project on the conduct of students. The collected data was analyzed using descriptive statistics and testing the differences by Multivariate ANOVA (MANOVA). The findings of the research revealed that the students joining the teacher preparation for local development project had self-conduct in the areas of characteristics, relationship with community, and spatial identity at high level. The means were 3.88, 3.72, and 3.81, respectively. The fourth-year students performed self-conduct at higher level than the second years with a significance level of .01. The third- and second-year students conducted differently in the areas of their attributes only. For the third and fourth years, there was no difference in their self-conduct.